Faithful quantum secure direct communication protocol against collective noise - 杨静 王川 张茹 (Chinese physics B, 2010)
An improved quantum secure direct communication （QSDC） protocol is proposed in this paper. Blocks of entangled photon pairs are transmitted in two steps in which secret messages are transmitted directly. The single logical qubits and unitary operations under decoherence free subspaces are presented and the generalized Bell states are constructed which are immune to the collective noise. Two steps of qubit transmission are used in this protocol to guarantee the security of communication. The security of the protocol against various attacks are discussed.